Answer f(t) = 7H(t) + bH(t-5) when t = 5 f(5) = 49 + 7b 15 = 49 + 7b -34 = 7b b = -34/7 Is it correct? Report Abuse
Follow Math Help Forum on Facebook and Google+
Originally Posted by mathsforumhelp Answer f(t) = 7H(t) + bH(t-5) when t = 5 f(5) = 49 + 7b 15 = 49 + 7b -34 = 7b b = -34/7 Is it correct? Report Abuse No. Did you plug your answer back into the original equation? Remember that $\displaystyle H(t-a)=\begin{cases} 0, \quad t < a \\ 1, \quad t > a\end{cases}$ You should find that $\displaystyle b=8$
View Tag Cloud